Sex, Conception Interval, Gestational Age, Apgar Score, and Anthropometric Surrogates in relation to Birth Weight of Bangladeshi Newborns: A Cross-Sectional Study. (8th May 2013) - Azhar, Bably Sabina; Monirujjaman, Md.; Islam, Kazi Saiful; Afrin, Sadia; Sabir Hossain, Md.
Abstract : In developing countries, where about 75% of births occur at home or in the community, logistic problems prevent the weighing of every newborn child. Baby born with a weight less than 2, 500 g is considered low birth weight, since below this value birth-specific infant mortality begins to rise rapidly. In Bangladesh, the prevalence of low birth weight is unacceptably high. Infant's sex differences, birth to conception interval, gestational age, and Apgar score are associated with infant birth weight. To screen low-birth-weight babies, simple anthropometric parameters can be used in rural areas where 80–90% of deliveries take place. A sample of 343 newborn singletons, 186 male and 157 female babies, were studied in Southwest region of Bangladesh to examine the birth weight status of newborns and to identify the relationship between birth weight and other anthropometric parameters of newborns. The mean birth weight was2754.81 ± 465.57  g, and 28.6% were low-birth-weight (<2, 500 g) babies. All key anthropometric parameters of the newborns significantly correlated with infant birth weight( P = 0.05 ) . Mid upper arm circumference and chest circumference were identified as the optimal surrogate indicators of LBW babies. In the community where weighing of newborns is difficult, these measurements can be used to identify the LBW babies.